Fatigue life of additively manufactured Ti–6Al–4V in the very high cycle fatigue regime. (January 2017) - Günther, J.; Krewerth, D.; Lippmann, T.; Leuders, S.; Tröster, T.; Weidner, A.; Biermann, H.; Niendorf, T.
Abstract: The present study reports on the impact of two different additive manufacturing routes, i.e. selective electron beam melting (EBM) and selective laser melting (SLM) on the fatigue life of the titanium alloy Ti–6Al–4V in the high cycle fatigue (HCF) and in the very high cycle fatigue (VHCF) regime. Cylindrical fatigue specimens were manufactured by EBM and SLM and tested in differently post-treated conditions. The EBM specimens were tested in the as-built condition, SLM manufactured specimens were heat treated at 800 °C and hot isostatically pressed, respectively. The type, size and location of every crack initiating discontinuity was determined and thoroughly investigated by scanning electron microscopy. Three main findings were derived from the present investigation. Fatigue properties of as-built EBM and stress relieved SLM specimens in the HCF and VHCF regimes are very similar. Defect types and defect sizes of similar nature were observed in both conditions. In consequence, stress relieving heat treatment has not to be conducted in EBM processed Ti–6Al–4V. The shape of the discontinuities, however, currently is not considered by traditional approaches for estimation of fatigue strength. The fatigue performance of the SLM processed and subsequently hot isostatically pressed condition is superior to its two additively manufactured counterparts and similar to conventionally processed material. Duplex S–N behavior with a clear transition area was observed in case of the Ti–6Al–4V specimens tested.